CT-guided radiofrequency ablation of osteoid osteoma and osteoblastoma: clinical success and long-term follow up in 77 patients - Rehnitz, Christoph; Sprengel, Simon David; Lehner, Burkhard; Ludwig, Karl; Omlor, Georg; Merle, Christian; Kauczor, Hans-Ulrich; Ewerbeck, Volker; Weber, Marc-André (European journal of radiology, 2012)
The purpose of this study was to retrospectively evaluate long-term success of CT-guided radiofrequency ablation (RFA) in patients with osteoid osteoma (OO) and osteoblastoma (OB) including tumors in critical locations. Eighty-one CT-guided RFA procedures were performed in 77 patients with OO (65 patients) and OB (12) including 6 spinal and 15 intra/periarticular tumors. Procedural techniques included multiple needle positions, three-dimensional access planning, as well as, thermal protection techniques. Long-term success was assessed using a questionnaire including, among others, several VAS (visual analogue scale) scores. All patients completed 3-6months follow-up, overall response to the questionnaire was 64/77 (83.1%). Primary success rate was 74/77 (96.1%) of all patients. Retreatment with RFA in 3 patients resulted in a secondary success rate of 77/77 (100%). Long-term follow-up (mean, 38.5months; range, 3-92) revealed a highly significant (p<0.001) reduction of all assessed limitation scores reaching normal or almost normal values. One major complication, a cannula break leading to a secondary short hospital stay, occurred. In conclusion, RFA is a safe and effective long-lasting treatment of OO and OB. Advanced procedural techniques aid treating tumors in critical locations and in the coverage of larger tumors. Besides night pain, RFA also greatly improves other factors negatively affecting the quality of life.
Gesehen am 30.04.2018